Experimental reduction of land use increases invertebrate abundance in grasslands - Staab, Michael; Keller, Alexander; Achury, Rafael; Hilpert, Andrea; Hölzel, Norbert; Prati, Daniel; Weisser, Wolfgang W.; Blüthgen, Nico (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Grasslands are diverse ecosystems that are increasingly threatened by intensive land use. Restoring grasslands by reducing land-use intensity may support insect abundance and diversity, helping to halt insect declines. To test for the effect of reduced land use on invertebrates, we studied an experiment (established 2020) at 45 sites across three regions of Germany. We hypothesized that reduced land use increases invertebrate abundance, with larger effects in less intensively used grasslands. Using suction sampling, invertebrates were quantitatively sampled in May 2021 and May 2023, with 2021 samples identified by DNA meta-barcoding. Reducing land use to a single late mowing increased invertebrate abundance by 41 % after one year and 99 % after three years. However, species diversity did not differ between treatments and controls. The effect of land-use reduction on abundance was consistently influenced by land use in the surrounding matrix, with larger positive effect sizes at grasslands with lower mowing frequency but higher fertilization. In spite of these local differences in the magnitude of restoration effects, the consistent increase in invertebrate abundance suggests that reducing land-use intensity can enhance invertebrate populations with potential benefits for ecosystem functions. It will be important to study how outcomes of land-use reduction develop over time, as land-use reduction is likely more successful when implemented permanently.
Keywords: Biodiversity; Fertilization; Grassland; Restoration; Grazing; Insect Decline; Mowing